Legal Regulation of Elementary and Upper Elementary Schools during the Second Czecho-Slovak Republic and the Protectorate of Bohemia and Moravia - Tereza Kolumber (Journal on European History of Law, 2023)
This paper offers an overview of the education law from 1760s to late 1930s and then well-structured analysis of the legal framework for elementary and upper elementary (main) schools from 1938 to 1945, which is characterized by a focus on extensive secondary legislation, which is frequently not even of the Czech origin. The paper intends to illustrate the transformation of the school system from the era of the interwar democratic state through a local variation of fascism into a Nazi-occupied territory where education was mainly intended to serve the indoctrination of children and youth. The author of the paper combines the available laws and regulations with other sources to provide a comprehensive overview of this part of the Czech education system, which has so far been rather neglected in the academic world.